Handbook of psychological change : psychotherapy processes & practices for the 21st century - Snyder, C. R. C.R. Snyder; Ingram, Rick E. Rick E. Ingram (New York : Wiley, 2000)
For example, Smith, Glass, and Miller (1980), in their precedent- setting review of therapeutic treatments, found that individual and group treatments were roughly equivalent in terms of effectiveness. Miller and Berman (1983) discovered that cognitive- behavioral treatments were more effective than other methods, irrespective of whether they were carried out in an individual or a group format. Similarly, Addie Fuhriman and Gary M. Burlingame (1994), after reviewing 700 group therapy
Includes bibliographical references and index.
Keywords: Psychotherapy; Change (Psychology); Psychotherapy -- Forecasting; Psychotherapy -- methods; Psychotherapy -- trends